THE USE OF CONTENT-BASED SUMMARIZING TECHNIQUE IN IMPROVING STUDENTS’ READING SKILLS OF MADRASAH - Zana Chobita Aratusa (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2017)
ABSTRACT Previous studies argued that summarizing techniques can improve students skill to comprehend a reading text, but those studies did not address what type of summarizing teachniques and how to apply them, in particular in Islamic schools context in which their studdents often study rich textual documents. Through the use of the experimental method, this study implemented Content-Based Summarizing Technique (CBST) in teaching English reading skill at two State Islamic Senior High Schools (Madrasah Aliyah Negeri) in Palu, Central Sulawesi. After 12 weeks teaching, this study found that students who were taught by using CBST have significantly improved their reading skill to comprehend a reading text. Meanwhile, the non-CBST treatment students’ reading skill remain stable. This study concludes that the use of CBST in English reading teaching can be used as a new alternative technique in English teaching. The limitation of this study is that the treatment might not be long enough and the sample small. Future research need to involve more sample and apply longer treatment period. ABSTRAK Sejumlah penelitian sebelumnya menemukan bahwa teknik merangkum dapat meningkatkan keterampilan siswa untuk memahami teks bacaan, namun penelitian tersebut tidak membahas jenis pengajaran yang meringkas dan bagaimana menerapkannya, khususnya dalam konteks sekolah Islam seperti madrasah yang para siswanya sering mempelajari berbagai teks bacaan. Dengan menggunakan metode eksperimen, penelitian ini menerapkan Content-Based Summarizing Technique (CBST) dalam pembelajaran keterampilan membaca dalam bahasa Inggris pada dua Madrasah Aliyah Negeri di Palu, Sulawesi Tengah. Setelah 12 minggu mengajar, penelitian ini menemukan bahwa siswa yang diajar dengan CBST mampu meningkatkan kemampuan membaca mereka secara signifikan dalam memahami teks bacaan dalam bahasa Inggris. Sementara itu, kemampuan membaca siswa yang tidak diajarkan dengan -CBST tetap tidak meningkat. Penelitian ini menyimpulkan bahwa penggunaan CBST dalam pengajaran membaca bahasa Inggris dapat digunakan sebagai teknik alternatif baru dalam pengajaran bahasa Inggris. Keterbatasan penelitian ini adalah lamanya penerapan CBST mungkin tidak cukup dan sampelnya kecil. Penelitian selanjutnya perlu melibatkan lebih banyak sampel dan periode penerapan CBST perlu lebih lama. How to Cite: Aratusa, Z. C. (2017). The Use of Content-Based Summarizing Technique in Improving Students’ Reading Skills of Madrasah. IJEE (Indonesian Journal of English Education), 4(2), 208-220. doi:10.15408/ijee.v4i2.6153